Pilomatricoma of cheek mimicking malignancy: A diagnostic challenge on Fine needle aspiration cytology (Indian Journal of Case Reports, 2019)
Pilomatricoma is a benign adnexal lesion which is often diagnosed on cytology. Sometimes cytomorphology may pose diagnostic challenge and may mimic malignant neoplasm. We present a case of a slow growing nodular swelling on the right upper cheek in a 9-year-old male child with similar diagnostic difficulty on Fine Needle Aspiration Cytology (FNAC).